2013
DOI: 10.1073/pnas.1312925110
|View full text |Cite
|
Sign up to set email alerts
|

H3R42me2a is a histone modification with positive transcriptional effects

Abstract: Histone posttranslational modification leads to downstream effects indirectly by allowing or preventing docking of effector molecules, or directly by changing the intrinsic biophysical properties of local chromatin. To date, little has been done to study posttranslational modifications that lie outside of the unstructured tail domains of histones. Core residues, and in particular arginines in H3 and H4, mediate key interactions between the histone octamer and DNA in forming the nucleosomal particle. Using mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
99
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 43 publications
8
99
0
Order By: Relevance
“…1A), potentially disrupting DNA-histone interactions. These observations, combined with previous results that H3K56ac and H3R42 trimethylation increase DNA unwrapping (26,37), suggest that H3Y41ph and H3T45ph may function to directly increase nucleosome unwrapping.…”
supporting
confidence: 71%
“…1A), potentially disrupting DNA-histone interactions. These observations, combined with previous results that H3K56ac and H3R42 trimethylation increase DNA unwrapping (26,37), suggest that H3Y41ph and H3T45ph may function to directly increase nucleosome unwrapping.…”
supporting
confidence: 71%
“…Both in in vitro reporter gene assay and in vivo infection experiments, we observed, repression owing to histone H3-arginine dimethylation by Rv1988. The difference in the results could be related to the use of synthetic chromatin in vitro transcription assay 34 versus the in vitro reporter gene assay and in vivo infection studies (this study). It is also possible that the difference was owing to symmetric versus asymmetric arginine dimethylation that is known to have opposite effects on transcription 36,37 .…”
Section: Discussionmentioning
confidence: 88%
“…A recent study showed by in vitro synthetic chromatin experiments that H3R42me 2, in presence of p53 and p300, acts to positively influence transcription 34 . On the other hand, in yeast, where a lysine is present instead of arginine at 42nd position, H3K42me 2 causes gene repression 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there were 858 down-regulated genes in the prmt6 severe morphant that included zygotic genes and demonstrated the failure of zygotic genome activation. Therefore, whether Prmt6 directly contributes to zygotic genome activation through generating active modifications, such as H4R3me2a and H3R42me2a (14,18), deserves to be investigated. Additional ChIP-sequencing studies are required to determine whether the misregulated genes (see supplemental Table 1A) are directly regulated by Prmt6.…”
Section: Discussionmentioning
confidence: 99%